دور تطبيقات الأجهزة الذكية في تعزيز العلاقة مع الزبون .دراسة عينة لمستخدمي بريدي موب - محمد الصالح،رزاق محسن; صلاح الدين ،بن عمارة; محمد البشير،سعيد; عمار،موساوي (university of eloued جامعة الوادي, 2024)
هدفت الدراسة إلى معرفة دور تطبيقات الأجهزة الذكية في تعزيز العلاقة مع الزبون بأبعادها (الموثوقية، سهولة الاستخدام، الأمان والسرية، والتأثير الاجتماعي )، ولقد قمنا بإجراء دراسة تطبيقية على عينة من مستخدمي تطبيق بريدي موب، واعتمدنا في هذه الدراسة على المنهج الوصفي التحليلي في جمع المعطيات والبيانات، ولتحقيق ذلك تم تصميم استمارة معلومات ووزعت على عينة 120فرد من المجتمع وتم استرجاع 100إستمارة صالحة للتحليل والمعالجة بواسطة البرنامج الاحصائي للعلوم الاجتماعيةSPSS ) )، لمعرفة اتجاه وقوة إجابات عينة الدراسة، وتوصلت الدراسة الى عدة نتائج أهمها: أن مستوى أبعاد مرتفع لدى تطبيق بريد موب بسبب وعي وعلم مؤسسة بريد الجزائر بولاية الوادي بأهمية هذه الأبعاد وحرصهم على تطوير خدمات المؤسسة وتحسين أدائها لتحقيق النجاح في ميدان العمل. وغالبية أفراد العينة راضون عن تجربتهم في استخدام تطبيقات الهواتف الذكية، يدل على سهولة وتنوع وجودة الخدمات الموجودة في التطبيقات والتي وفرت على الأفراد عناء التنقل إلى المؤسسة. لذلك لا توجد اختلافات بين اجابات المبحوثين فيما يتعلق بالجنس والعمر، في حين توجد اختلاف فيما يتعلق بباقي المتغيرات الشخصية (المستوى التعليمي). The study aimed to know the role of smart device applications in strengthening the relationship With the customer's dimensions reliability ease of use security, confidentiality, and impact for social), and we have conducted an applied study on a sample of users of Application of Baridi Mob In this study, we relied on the descriptive approach Analytical in the collection of data and data and to achieve this a form was designed Information was distributed to a sample of 120 members of the community and 1100 were retrieved A valid form for analysis and processing by the statistical program for scientific sciences Social (SPSS), to know the direction and strength of the answers of the study sample, as reached The study to several results, the most important of which are: 1-level High dimensions at Baridi Mob due to the awareness and knowledge of an organization Algeria Post in El-Oued province of the importance of these dimensions and their keenness to develop Enterprise services and improving its performance to achieve success in the field of work. 2-The majority of respondents are satisfied with their experience in using mobile applications Smart, indicates the ease, diversity and quality of services found in Applications, which saved individuals the trouble of navigating to the organization. 3-There are no differences between respondents' answers regarding gender and age While there is a difference with respect to the rest of the personal variables (Educational level).
Keywords: أجهزة الذكية; هواتف ذكية; تطبيقات أجهزة ذكية; زبون; smart devices; smart phones; smart device applications; the customer